MANDATORY CORPORATE SOCIAL RESPONSIBILITY IN INDONESIA - Laurensia Andrini (Fakultas Hukum Universitas Gadjah Mada, 2016)
AbstractRegulation on CSR under laws and regulations of Company Act have not given clarity and legal certainty as it does not stipulate sanction and control mechanism. In the practical level, the implementation of CSR is often mistargeted because the company does not have a clear guidance to fulfill people’s demand. It is the purpose of this research to understand how far CSR is obligatory towards Limited Liability Companies who perform business in the field of and or related to natural resources as well as to understand the reason behind mandatory CSR in Indonesia. IntisariPeraturan mengenai Tanggung Jawab Sosial dan Lingkungan yang diatur dalam peraturan perundang-undangan mengenai Undang-undang Perseroan Terbatas belum memberikan kejelasan dan kepastian hukum karena tidak adanya sanksi dan mekanisme pengawasan. Dalam ranah praktis, penerapan TJSL seringkali kurang tepat sasaran karena Perseroan Terbatas tidak memiliki panduan yang jelas untuk memenuhi permintaan masyarakat. Penelitian ini ditujukan untuk memahami sejauh mana kewajiban TJSL terhadap Perseroan Terbatas yang melakukan usaha di bidang atau terkait dengan sumber daya alam, sekaligus untuk memahami alasan di balik kewajiban TJSL di Indonesia.